THE APPLICATION OF MODERN TEACHING METHODS IN LANGUAGE EDUCATION - Zamira Usmonova (Bright Mind Publishing, 2025)
This article explores the integration and effectiveness of modern teaching methods in language education, focusing on their practical implementation within the philological faculties of higher education institutions in Uzbekistan. As global educational systems shift toward learner-centered instruction, the use of innovative strategies—such as task-based learning, communicative approaches, flipped classrooms, and digital platforms—has become increasingly relevant. The article discusses how these methodologies contribute to developing students’ communicative competence, critical thinking, and autonomous learning skills. Moreover, it addresses the institutional readiness, teacher training, and technological infrastructure required to ensure successful adoption. Drawing on both theoretical perspectives and practical applications, this study offers a comprehensive view of modern language pedagogy in contemporary higher education.
Keywords: Language education, modern teaching methods, communicative approach, task-based learning, flipped classroom, digital pedagogy, higher education, philology, teacher training.